PERSISTENT SYMPTOMS IN PATIENTS AFTER ACUTE COVID-19 INFECTION": A SINGLE CENTER EXPERIENCE: ARE WE DOING ENOUGH FOR THIS? - CHACHAR, AZK; QURESHI, SR; ALVI, AH; SOHAIB, M; ALI, S; ULFAT, M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the frequency of persistent COVID-19 symptoms after recovery from the infection. The study design was cross-sectional and conducted at the Department of Medicine, Fatima Memorial Hospital, Lahore. A non-probability consecutive sampling technique was employed, and the study duration was six months (from 28th June 2021 to 27th December 2021) after approval from the ethical committee. The sample size was 400. The study found that symptoms persisted for varying durations of less than one week, one to two weeks, two to four weeks, and more than four weeks. The most common persistent symptoms were lethargy (70.6%), body aches (55%), and cough (50%). The symptoms that persisted for more than four weeks were hair fall (71%), loss of smell and taste (53%), and body aches (43%). The mean duration of illness was two to four weeks from the start of the disease. The study concluded that COVID-19 infection was associated with residual symptoms that could persist for more than four weeks and affect patients’ quality of life, interfering with daily life activities.